Non-suicidal self-injury and its risk factors among Iranian high school and university students - Abbasi-Ghahramanloo, Abbas; Khodadoust, Behnam; Adham, Davoud; Gholami, Ali; Farokhi, Roya; Maghsodlou-Nejad, Vahid; Afrashteh, Sima (Frontiers in Psychiatry, 2024)
Background: Non-suicidal self-injury (NSSI) is an important health problem among adolescents and young adults. The aims of this study were to determine NNSI status and its associated factors among students.This cross-sectional study has been conducted in 5100 4715 high school and university students from the West and Northwest provinces of Iran. Multi-stage sampling was used to select students and all students completed survey questionnaires. Data analysis was performed using chi-square, Fisher's exact test, binary and logistic regression.The lifetime prevalence of NSSI was estimated as 24.4% among all participants (21.4% in high school students vs. 29.3% in university students). After adjustment for other factors, age (OR=1.08,95%CI:1.03-1.12), cigarette smoking as an experimenter (OR=1.94,95%CI:1.61-2.34) and regular (OR=3.80,95%CI:2.96-4.89) compared to nonsmokers, membership in a sport team (OR = 1.26,95%CI:1.08-1.48), having physical fight (OR = 2.18,95%CI:1.85-2.57), doing general risk taking behavior (OR = 2.05,95%CI:1.66-2.53), and self-esteem (OR=0.93,95%CI:0.92-0.95) were associated with experience of NSSI.Our results suggested that the prevalence of NSSI was relatively high among high school and university students. To diagnose, prevent, and treat NSSI in teenagers and young adults in Iran, more research is needed to identify the root causes.Specific programs including some educational workshops about NSSI and other risk taking behaviors for students and their parents could be effective in enhancing student's knowledge toward these behaviors and possible reduction in NSSI prevalence.